Follicular fluid adenosine deamines (ADA), superoxide dismutase and nitric oxide levels in GnRH agonist and antagonist cycles - Celik, E.; Celik, O.; Kumbak, B.; Yilmaz, E.; Turkcuoglu, I.; Simsek, Y.; Tanbek, K. (Oxford Univ Press, 2012)
[Abstract Not Available]
28th Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE) -- JUL 01-04, 2012 -- Istanbul, TURKEY